Impact of Obstructive Sleep Apnea in Patients with Acute Heart Failure: A Nationwide Cohort Study - Abdulmajeed Alharbi; Nahush Bansal; Anas Alsughayer; Momin Shah; Waleed Alruwaili; Mohammed Mhanna; Halah Alfatlawi; Eun Seo Kwak; Ayman Salih; Mohanad Qwaider; Ragheb Assaly (Hearts)
Background/Objectives: Heart failure presents a significant public health challenge, affecting millions in the US, with projections of increasing prevalence and economic burdens. Obstructive sleep apnea (OSA) is highly prevalent among HF patients. This study analyzes the impact of OSA on the outcomes in patients admitted with acute decompensated heart failure. Methods: We conducted a retrospective cohort study using the National Inpatient Sample database (NIS) 2020, focusing on patients admitted with acute heart failure. Patient outcomes were compared between those with and without a secondary diagnosis of OSA, identified via validated ICD-10 codes. Subgroup analysis was conducted between heart failure patients with reduced ejection fraction (HFrEF) and preserved ejection fraction (HFpEF). Results: Among 65,649 patients with acute heart failure, 4595 (7%) patients were found to have OSA. The patients with OSA were more likely to be male, older in age and had a higher burden of comorbidities. No significant differences were observed in mortality between heart failure patients with and without OSA. In HFrEF patients, OSA was associated with longer hospital stays (6.45 days vs. 5.79 days, p < 0.001), higher rates of acute kidney injury (AKI) (adjusted odds ratio 1.28, 95% CI: 1.07–1.54, p = 0.007), and atrial fibrillation (adjusted odds ratio 1.35, 95% CI: 1.13–1.61, p = 0.001). In HFpEF patients, an association between OSA and AF was observed (adjusted odds ratio 1.20, 95% CI: 1.01–1.42, p = 0.03). Conclusions: OSA is associated with poor in-hospital outcomes in patients admitted with acute heart failure. HFrEF subgroup is especially vulnerable, with OSA leading to a significant increase in healthcare utilization and complication rates in these patients. This nationwide study underscores the importance of timely identification and treatment of OSA in heart failure to alleviate healthcare burdens and improve patient outcomes.